SILAS MALAFAIA: SEUS DESEJOS E MODELOS Um estudo a partir da teoria do desejo mimético de René Girard - SOUZA, GIDEANE MORAES DE (2016)
This dissertation presents the results of research on Silas Malafaia - a well-known lecturer between evangelicals and among non- evangelicals in Brazil that uses the TV feature for about 33 years , where it holds programs with different formats over the years ; and an incisive speech relevant influence on many followers . His preaching condemns abortion , drug use and what sees as increasing the privileges of homosexuals , while he took the theology of prosperity. Using the theory of Mimetic Mechanism René Girard , and studying the context in which it was created and who was related from its beginnings , this research studies the evolution and positioning changes Silas Malafaia and the influence of his desire models. We will analyze in particular the transition to a more conservative theology Assembly of God to join the Positive Confession and Prosperity Theology, and the use of media not only toward Christians, but as a trade tool , which once fought . It started from the hypothesis that Silas Malafaia change his speech and preaching in that it takes as models of desire televangelists American pastors , as Morris Cerullo and Mike Murdock , who work in television media and are considered successful pastors. That the analysis , we differentiate two types of desire models - according to the mimetic desire theory of René Girard - in the life of Silas Malafaia : internal mediation models and external mediation. It is hoped that this work can contribute to the reflections on René Girard 's theory and for studies concerning the Assembleiano Pentecostalism and its various possibilities.